2009
DOI: 10.1007/s11999-009-0805-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the Remnant Femoral Attachment of the Ruptured ACL

Abstract: The presence of remnant tibial and femoral attachments of the ruptured ACL has been described in the literature but the femoral remnant has not been well described as a landmark for tunnel placement during reconstruction. We reviewed operative reports, pictures, and videotapes from 111 ACL reconstructions to determine the incidence of a remnant femoral stump. Patients were divided into two groups: Group A included patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Soft tissue remnants of the ACL stumps, rupture pattern, and anatomical landmarks such as the lateral bifurcate and intercondylar ridges of the femur (present in 98% of cases) have been shown to be critical components for defining the native ACL anatomy. 8,9,20,[26][27][28] Recent publications have recommended single-bundle ACLR instead of a double-bundle ACLR in cases where the ACL insertion site is 14 mm in length. 19 Furthermore, the size of ACL insertion sites may influence the size of the graft and thus the graft choice, as certain grafts may limit the ability to restore the native insertion site size.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue remnants of the ACL stumps, rupture pattern, and anatomical landmarks such as the lateral bifurcate and intercondylar ridges of the femur (present in 98% of cases) have been shown to be critical components for defining the native ACL anatomy. 8,9,20,[26][27][28] Recent publications have recommended single-bundle ACLR instead of a double-bundle ACLR in cases where the ACL insertion site is 14 mm in length. 19 Furthermore, the size of ACL insertion sites may influence the size of the graft and thus the graft choice, as certain grafts may limit the ability to restore the native insertion site size.…”
Section: Discussionmentioning
confidence: 99%
“…A graft-size-appropriate cannulated reamer was used to create the tibial tunnel. Using the anteromedial portal, the femoral tunnel was placed by positioning the guide (Retro-Drill, Arthrex, Naples, FL) near the center of the ACL footprint, as estimated visually by the surgeon (Kaseta 2008; Wittstein 2009). A guide-pin was placed from outside the joint through a small incision over the lateral femoral cortex just proximal to the lateral femoral condyle and anterior to the intermuscular septum.…”
Section: Methodsmentioning
confidence: 99%
“…Crain et al, and Lo et al observed 18 reattachments out of 48 cases and 67 reattachments out of 101 cases, respectively . In contrast, Murray et al and Wittstein et al reported that in all cases that the tibial ACL remnant was resorbed and a reattachment of the ACL remnants was not present in any of the cases. This difference in the incidence of reattachments may be explained by the difference in injury mechanism between the patients, which could result in a difference in tibial ACL remnant length and in turn in the chance to reattach.…”
Section: Discussionmentioning
confidence: 97%